Some techniques for the study of useful characters in the taxonomy of the genus Timarcha Samouelle, 1819 (Coleoptera, Chrysomelidae) - Daccordi, Mauro; Bollino, Maurizio; Vela, José Miguel (European Journal of Taxonomy, 2020)
Historically the taxonomy of the genus Timarcha has been, and continues to be, quite confusing and largely erroneous. The confusion is mainly due to the absence of reliable traits that aid in precise identification; the lack of study of types at species-level has also contributed to the difficulty in the taxonomy. To improve this situation, we propose techniques for the dissection and study of three useful diagnostic characters such as the vestiture of the sole of female tarsi, and the morphology of the endophallus and its sclerites in males. These features combined are distinctive for each of the species and can help to resolve the taxonomy of the genus.